2013
DOI: 10.1007/s00464-012-2746-x
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of the morbidity and mortality of gallbladder surgery in the elderly

Abstract: Emergency gallbladder surgery in the elderly was not associated with higher mortality or complication rate compared with the elective setting. Elderly patients with gallbladder-related emergencies should be offered urgent surgery when feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Supporting our data, McGillicuddy et al found that there was no significant difference in sex distribution in elderly patients with AC (11). McKay et al also reported similar results in elderly patients with AC who had undergone surgery (12).…”
Section: Discussionsupporting
confidence: 88%
“…Supporting our data, McGillicuddy et al found that there was no significant difference in sex distribution in elderly patients with AC (11). McKay et al also reported similar results in elderly patients with AC who had undergone surgery (12).…”
Section: Discussionsupporting
confidence: 88%
“…In line with our study, a study observed no significant differences of gender in old age AC patients 17 . In another research, similar findings were reported in AC old age patients as compared with middle age patients 18 .…”
Section: Discussionsupporting
confidence: 80%
“…In Europe alone, almost 30% of the population is predicted to be aged 65 or over by 2050 [ 20 ]. Geriatric patients frequently undergo emergency general surgery and accrue more postoperative complications and fatal outcomes than the general population [ 5 , 13 , 16 ]. It is thus highly relevant to develop and guide evidence-based patient-centered decision-making around emergency surgical care [ 21 ].…”
Section: Discussionmentioning
confidence: 99%